The effect of isometric handgrip exercise on blood pressure reduction in hypertensive patients: A literature review - Isnaeni, Alfi Nur; Muhlisin, Abi (Institute of Computer Science (IOCS), 2025)
High blood pressure remains a significant non-communicable disease that continues to rise within society. Known as a silent disease, it can lead to complications with other conditions, causing various symptoms and discomfort for sufferers. While numerous pharmacological therapies have been implemented, they often fall short of effectively addressing this condition. Consequently, additional supportive therapies are required, such as Isometric Handgrip Exercise, which is an easy and cost-effective method that can be performed independently without special training. Articles were sourced from ScienceDirect, PubMed, and the Directory of Open Access Journals using advanced search terms like